A perspective on the bright future of metal halide perovskites for X-ray detection - Sytnyk, Mykhailo; Deumel, Sarah; Tedde, Sandro Francesco; Matt, Gebhard; Heiß, Wolfgang (Applied Physics Letters, 2019)
Metal halide perovskites (MHPs) changed the world of solution processed semiconductors, previously dominated by organic semiconductors, toward predominantly inorganic materials with a relatively high electron/hole mobility. A series of devices benefit from their optoelectronic properties, including X-ray detectors. After the introduction of MHP X-ray detectors in 2013, they have achieved significant improvements in the form of single crystals, polycrystalline materials, and pixelated imaging devices. In addition, MHPs in the form of colloidal nanocrystals act as excellent scintillators. We see the bright future of MHPs in energy resolved X-ray detection, either achieved in the single counting mode, or in nanocrystal multilayer stacked devices, acting as a combination of selective X-ray filters and scintillators.
CRIS-Team Scopus Importer:2019-11-15

High-sensitivity high-resolution X-ray imaging with soft-sintered metal halide perovskites - Deumel, Sarah; Van Breemen, Albert; Gelinck, Gerwin; Peeters, Bart; Maas, Joris; Verbeek, Roy; Shanmugam, Santhosh; Akkerman, Hylke; Meulenkamp, Eric; Huerdler, Judith E.; Acharya, Manognya; Garcia-Batlle, Marise; et al. (Nature Electronics, 2021)
To realize the potential of artificial intelligence in medical imaging, improvements in imaging capabilities are required, as well as advances in computing power and algorithms. Hybrid inorganic–organic metal halide perovskites, such as methylammonium lead triiodide (MAPbI3), offer strong X-ray absorption, high carrier mobilities (µ) and long carrier lifetimes (τ), and they are promising materials for use in X-ray imaging. However, their incorporation into pixelated sensing arrays remains challenging. Here we show that X-ray flat-panel detector arrays based on microcrystalline MAPbI3 can be created using a two-step manufacturing process. Our approach is based on the mechanical soft sintering of a freestanding absorber layer and the subsequent integration of this layer on a pixelated backplane. Freestanding microcrystalline MAPbI3 wafers exhibit a sensitivity of 9,300 µC Gyair–1 cm–2 with a μτ product of 4 × 10–4 cm2 V–1, and the resulting X-ray imaging detector, which has 508 pixels per inch, combines a high spatial resolution of 6 line pairs per millimetre with a low detection limit of 0.22 nGyair per frame.
CRIS-Team Scopus Importer:2021-10-01

Self-Healing Cs3Bi2Br3I6 Perovskite Wafers for X-Ray Detection - Daum, Manuel; Deumel, Sarah; Sytnyk, Mykhailo; Afify, Hany A.; Hock, Rainer; Eigen, Andreas; Zhao, Baolin; Halik, Marcus; These, Albert; Matt, Gebhard; Brabec, Christoph; Tedde, Sandro F.; et al. (Advanced Functional Materials, 2021)
Self-healing of defects imposed by external stimuli such as high energy radiation is a possibility to sustain the operational lifetime of electronic devices such as radiation detectors. Cs3Bi2Br3I6 polycrystalline wafers are introduced here as novel X-ray detector material, which not only guarantees a high X-ray stopping power due to its composition with elements with high atomic numbers, but also outperforms other Bi-based semiconductors in respect to detector parameters such as detection limit, transient behavior, or dark current. The polycrystalline wafers represent a size scalable technology suitable for future integration in imager devices for medical applications. Most astonishingly, aging of these wafer-based devices results in an overall improvement of the detector performance—dark currents are reduced, photocurrents are increased, and one of the most problematic properties of X-ray detectors, the base line drift is reduced by orders of magnitude. These aging induced improvements indicate self-healing effects which are shown to result from recrystallization. Optimized synthetic conditions also improve the as prepared X-ray detectors; however, the aged device outperforms all others. Thus, self-healing acts in Cs3Bi2Br3I6 as an optimization tool, which is certainly not restricted to this single compound, it is expected to be beneficial also for many further polycrystalline ionic semiconductors.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bismuth halides; lead-free perovskites; photoconductors; self-healing; X-ray detection